A new species of Cedria Wilkinson (Hymenoptera: Braconidae: Lysiterminae) from Thailand - Quicke, Donald L. J.; Belokobylskij, Sergey A.; Raweearamwong, Marisa; Butcher, Buntika A. (Zootaxa, 2017)
The Old World, cyclostome braconid wasp genus Cedria Wilkinson is recorded from Thailand for the first time based on a new species, Cedria wichasei Quicke, Belokobylskij & Butcher, sp. nov., which is described, illustrated, and a key provided to enable its separation from the closely-related species, C. galinae Belokobylskij and C. africana Belokobylskij which share strong peri-occular carina and at least rather rugose frons. Similarities to Apocedria van Achterberg & Chen, from China, are discussed.